2010
DOI: 10.1175/2010jcli3347.1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of North Atlantic–Arctic Multidecadal Variability on Northern Hemisphere Surface Air Temperature

Abstract: The 20

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(96 citation statements)
references
References 33 publications
6
85
0
5
Order By: Relevance
“…This view is supported by model results that relate the variability of the global-mean SST to North Atlantic thermohaline circulation (30,31,35) and by the existence of an AMO-like variability in control runs without anthropogenic forcing (28). If this conclusion is correct, then the following interpretation follows: The anthropogenic warming started after the mid-19th century of Industrial Revolution.…”
Section: Resultsmentioning
confidence: 85%
“…This view is supported by model results that relate the variability of the global-mean SST to North Atlantic thermohaline circulation (30,31,35) and by the existence of an AMO-like variability in control runs without anthropogenic forcing (28). If this conclusion is correct, then the following interpretation follows: The anthropogenic warming started after the mid-19th century of Industrial Revolution.…”
Section: Resultsmentioning
confidence: 85%
“…The circulation changes accompanying the shift toward the warm polarity of the ENSO cycle (or Pacific Decadal Oscillation) (21) (5-7). In a similar manner, the strengthening of the thermohaline circulation in the North Atlantic from the early 1970s onward favored a trend in the positive polarity of the North Atlantic Oscillation and warmer winters over high latitudes of Eurasia (22,23). Over such short time intervals and restricted spatial domains, the variability generated by the internal dynamics of the climate system can overwhelm the anthropogenically forced variability (24).…”
Section: Discussionmentioning
confidence: 88%
“…Compo and Sardeshmukh (2009) found that the recent worldwide land warming has a significant component originating from warmer oceans rather than being a direct effect of increasing greenhouse gases. Semenov et al (2010) estimated the AMO contribution to post 1970 global warming to be 0.24°C. Tung and Zhou (2013) found that neglecting the AMO leads to an overestimation of the global mean anthropogenic warming trend during the second half of the twentieth century by about a factor of two.…”
Section: Introductionmentioning
confidence: 99%